(untitled) (Research, Society and Development, 2021)
This study aims to analyze the epidemiological profiles of Visceral Leishmaniasis (VL) and Visceral Leishmaniasis-HIV (VL-HIV) co-infection in the state of Piauí, from 2007 to 2019. The research method used was the descriptive epidemiological study, of the quantitative type, regarding the epidemiological profile of cases of visceral leishmaniasis and LV-HIV co-infection in Piauí from 2007 to 2019, notified and confirmed in the SINAN (Information System for Notifiable Diseases). Of the 2,797 cases of visceral leishmaniasis notified, the “white/ignored” cases (n=486) marked in subfield 34 of the SINAN LV notification form were discarded, totaling a sample of 2,311 cases, of which 2015 (87.2%) had only LV and 296 (12.8%) LV-HIV co-infection. In Piauí, VL is considered a serious public health problem and it was found that patients with visceral leishmaniasis with and without HIV co-infection were mostly men and from urban areas, aged 1 to 4 years for VL and 20 to 39 years for LV-HIV, with the main method of laboratory confirmation in both groups, with a good percentage of cure (80%), a high lethality (10.13%) and recurrence (10%).